ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT UPAH PEKERJA DI ACEH - Miswar Miswar (Jurnal Ekonomi dan Kebijakan Publik Indonesia, 2018)
AbstractThe purpose of this study wanted to know the factorsthat affect the level of wages and determine the influenceof each factor on the level of wages in Aceh. This studyuses multiple regression analysis techniques. The surveyresults revealed significant factors affecting the level ofwages is education, type of work, hours of work andwork experience. All these factors have a positive effecton the number of workers' wages. Education increasesone year would increase wages by 49 983 rupiah.Professional workers have higher wages amounting to949 009 rupiah compared skilled workers. Workinghours increase by 1 hour will increase wages by 20 115rupiah. Workers who already have experience to havehigher wages for 133 766 rupiah compared to workerswho do not have experience. To improve the welfare ofgovernment workers have to ensure companies paywages above the provincial minimum wage.